Izvajanje lokalnih javnih služb: (31. maj 2016, Ljubljana, Slovenija) : konferenčni zbornik - Brezovnik, Boštjan (2016)
Local Public Services Provision : (31. maj 2016, Ljubljana, Slovenija) : konferenčni zbornik. This collection of conference papers include scientific papers presented by scholars dedicated to the study of public services at the conference on Local Public Services Provision in Ljubljana. The central topic of this conference was the provision of the local public services in Slovenia.